Bit-based cube rotation for text encryption - Rihartanto Rihartanto; Didi Susilo Budi Utomo; Herny Februariyanti; Arief Susanto; Wardatul Khafidhah (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Today's rapid technological developments make information increasingly important. Not just its content, but the channels or media used for information distribution also need to be secured. Information security is an important aspect that requires serious attention. One of the most important parts of information security is implementation of encryption using certain methods or techniques. This study proposes bit-based cube rotation to secure a plaintext. The aim is to produce a ciphertext that satisfies the two properties of cryptography through diffusion to produce confusion. The result shows that in a normal sentence, there is a significant change in the ciphertext which has the highest avalanche effect value of 55.47% and a correlation coefficient of 0.115. This result proves that the bit-based cube rotation can produce a good ciphertext, where the encryption result is not influenced by its original text.